Penguatan Literasi Membaca dengan Menggunakan Pop Up Book di Rumah Baca Rambutan Medan - Matondang, Fatimah Zahra; Pasaribu, Arda Yatul Liani; Mariana; Sari, Wulan Tahnia; Harahap, Febriza Wirahma Dina; Yani, Sarah Syafra; Siregar, Disna Anum; Siregar, Nurhafni (Indo-MathEdu Intellectuals Journal, 2024)
The low economic condition of the population in Bandar Selamat Subdistrict, Medan City has caused the children there to drop out of school. This caused several local youths to take the initiative to build the Rambutan Reading House as a learning forum for children to continue receiving an education. The aim of this leadership project activity is to strengthen the reading literacy of the children of Rambutan Reading House using Pop Up Book media. The data collection techniques used observation, interviews and documentation with twenty children as research subjects. The results of this activity show the enthusiasm of the children of Rambutan Reading House in reading literacy activities using Pop Up Book media. Apart from that, they are also able to retell the contents of the story and answer all the questions correctly during quiz games